Vietnam's Political Process: How education shapes political decision making, 1st edition - Lucius, Casey (Routledge, 2020)
In a system that is known for its covert political style, Vietnam’s decision making process is often described as either consensus-based or simply confusing and inexplicable. This book provides an approach to understanding political decision making in Vietnam by recognizing enduring values that are derived from State-controlled education and official historical narratives.